2022
DOI: 10.1002/kjm2.12518
|View full text |Cite
|
Sign up to set email alerts
|

Finite nucleos(t)ide analogue therapy in hepatitis B e antigen‐negative chronic hepatitis B: From an “option” to an “active recommendation”

Abstract: Nucleos(t)ide analogue (Nuc) including entecavir, tenofovir disoproxil fumarate, and tenofovir alafenamide may suppress hepatitis B virus (HBV) DNA profoundly but have no direct action on covalently closed circular DNA, which is a very stable template for HBV production. Therefore, decades of long-term Nuc therapy are required to maintain HBV suppression and to achieve hepatitis B surface antigen (HBsAg) loss in hepatitis B e antigen (HBeAg)-negative patients. However, there are concerns including financial bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Moreover, different biochemical criteria of retreatment have been applied in the previously published studies making difficult to compare and obtain solid conclusions. 79 , 90 , 92 , 100 However, our recommendation is in consonance with Liaw and Chien advice 86 , 101 that retreatment criteria should not be determined at one single time point and careful and close assessment is required to better define the type of hepatitis flare for optimal retreatment decision.…”
Section: New Perspectives On Nucleos(t)ide Analogues Cessationsupporting
confidence: 54%
“…Moreover, different biochemical criteria of retreatment have been applied in the previously published studies making difficult to compare and obtain solid conclusions. 79 , 90 , 92 , 100 However, our recommendation is in consonance with Liaw and Chien advice 86 , 101 that retreatment criteria should not be determined at one single time point and careful and close assessment is required to better define the type of hepatitis flare for optimal retreatment decision.…”
Section: New Perspectives On Nucleos(t)ide Analogues Cessationsupporting
confidence: 54%
“…Without concrete data to directly assess the outcomes of such a practice, there is no basis for discussion and it might be argued that the policy is the new paradigm. 28,29 To enhance the generalizability…”
Section: Discussionmentioning
confidence: 99%
“…This population‐based study offers empirical evidence that challenges the restrictive policy on NUC reimbursement in Taiwan. Without concrete data to directly assess the outcomes of such a practice, there is no basis for discussion and it might be argued that the policy is the new paradigm 28,29 . To enhance the generalizability of our study, we not only excluded patients with cirrhosis or portal hypertension but also identified a sub‐cohort of “eligible” patients to stop NUCs.…”
Section: Discussionmentioning
confidence: 99%
“…Effective nucleos(t)ide therapies to suppress hepatitis B DNA are available for patients with chronic viral hepatitis B; however, long-term therapy may be problematic in regions with limited resources. Identification of individuals who can safely discontinue nucleos(t)ide analog therapy is a significant unmet need until higher rates of functional cure are attained 67 . Interferon is administered for a limited time with a higher rate of HBsAg clearance, but it is difficult for some individuals to tolerate, and many populations have inadequate response rates.…”
Section: Opportunities For Clinical Trials To Address Societal and Me...mentioning
confidence: 99%
“…Identification of individuals who can safely discontinue nucleos(t)ide analog therapy is a significant unmet need until higher rates of functional cure are attained. [67] Interferon is administered for a limited time with a higher rate of HBsAg clearance, but it is difficult for some individuals to tolerate, and many populations have inadequate response rates. Even with longer durations of therapy with nucleos(t)ide analogs, HBsAg loss or functional cure is uncommon, and the greatest unmet therapeutic need is to combine therapies that target replication and modulate immunity to achieve high rates of functional cure with finite durations of therapy.…”
Section: Opportunities For Clinical Trials To Address Societal and Me...mentioning
confidence: 99%